2017
DOI: 10.1038/s41598-017-11275-0
|View full text |Cite
|
Sign up to set email alerts
|

Next generation highly resistant mirrors featuring all-silica layers

Abstract: A principal possibility to overcome fundamental (intrinsic) limit of pure optical materials laser light resistance is investigated by designing artificial materials with desired optical properties. We explore the suitability of high band-gap ultra-low refractive index material (n less than 1.38 at 550 nm) in the context of highly reflective coatings with enhanced optical resistance. The new generation all-silica (porous/nonporous) SiO2 thin film mirror with 99% reflectivity was prepared by glancing angle depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Compared to capillaries, gas-filled multipass cells allow very efficient compression, longer propagation distances, and larger beam sizes. Moreover, progress in mirror coating technologies, with a damage threshold increasing over the years [19] and dispersion management capabilities over broader bandwidths [20], suggests that this technique could be used advantageously in a large number of ultrafast laser systems. The overall agreement between our experimental data with a 3D numerical model describing the propagation is excellent, including the absence of spatio-temporal couplings.…”
Section: Compares the Results Ofmentioning
confidence: 99%
“…Compared to capillaries, gas-filled multipass cells allow very efficient compression, longer propagation distances, and larger beam sizes. Moreover, progress in mirror coating technologies, with a damage threshold increasing over the years [19] and dispersion management capabilities over broader bandwidths [20], suggests that this technique could be used advantageously in a large number of ultrafast laser systems. The overall agreement between our experimental data with a 3D numerical model describing the propagation is excellent, including the absence of spatio-temporal couplings.…”
Section: Compares the Results Ofmentioning
confidence: 99%
“…It becomes possible to make strongly birefringent thin films by GLAD using optically isotropic Si and SiO 2 materials [6]. It was recently demonstrated that such films have larger visible and near-infrared (near-IR) laser damage thresholds in J/cm 2 compared to polished surfaces or coatings made out of the two different materials [7]. GLAD deposited thin films can also act as an antireflection coating [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It becomes possible to make strongly birefringent thin films by GLAD using optically isotropic Si and SiO 2 materials [6]. It was recently demonstrated that such films have larger visible and near-infrared (near-IR) laser damage thresholds in J/cm 2 compared to polished surfaces or coatings made out of the two different materials [7]. GLAD deposited thin films can also act as an antireflection coating [8,9].…”
Section: Introductionmentioning
confidence: 99%